Democritus : science, the arts, and the care of the soul : proceedings of the International Colloquium on Democritus, Paris, 18-20 September 2003 - Brancacci, Aldo.; Morel, Pierre-Marie. (Philosophia antiqua,, 2007)
This volume gathers the papers presented at an International Colloquium held in Paris in 2003, and offers new contributions and new interpretative suggestions about both canonical and relatively neglected research areas on Democritus, including ethics, physics and epistemology, as well as musical and literary criticism, technics, zoology, and the catalogue of works. Specific contributions are furthermore devoted to Democritus' posterity and the problem of sources. The book also offers a detailed bibliography and several indices, which render it an up-to-date and stimulating tool for contemporary research on Democritus and atomism. Essays by: A. Brancacci, L. Gemelli, A. Jaulin, W. Leszl, J. Mansfeld, P.-M. Morel, D. O'Brien, L. Perilli, J. Salem, C.C.W. Taylor, J. Warren.